Aspects associated with health care professionals’ digital health competence development – a qualitative study - Jarva, Erika; Mikkonen, Kristina; Andersson, Janicke; Tuomikoski, Anna-Maria; Kääriäinen, Maria; Meriläinen, Merja; Oikarinen, Anne (Finnish Journal of eHealth and eWelfare, 2022)
Health care professionals need continuous education to maintain the competencies required to provide high-quality care; in today’s world, this means an understanding of digital health services. Insight into health care professionals’ experiences of which aspects influence their digital health competence development is therefore highly relevant. The objective of the study was to examine which aspects influence the digital health competence development of health care professionals (nursing workforce and allied health professionals). In-depth, semi-structured interviews were conducted with 20 health care professionals (Finland n=15, Sweden n=5) from various health care settings between May 2019 and July 2020. Interviews were audio-recorded, translated verbatim and analysed with inductive content analysis. Health care professionals perceive that digital health competence development is influenced by aspects related to digital health adoption, co-workers and the work community, their manager, and opportunities for continuous education and orientation. The participants agreed that digital health competence is an important part of a health care professional’s overall clinical competence. Continuous education geared towards digital health competence should be systematically designed, and potentially integrate the resources available on social media platforms. Additionally, managers and supervisors should take a stronger stance towards learning about digital health services so they can serve as role models to their employees and genuinely promote digital health competence development.